Degree of conversion and bond strength of resin-cements to feldspathic ceramic using different curing modes - Veridiana Resende NOVAIS; Luís Henrique Araújo RAPOSO; Rafael Resende de MIRANDA; Camila de Carvalho Almança LOPES; Paulo Cézar SIMAMOTO JÚNIOR; Carlos José SOARES
Abstract Resin cements have led to great advances in dental ceramic restoration techniques because of their ability to bond to both dental structures and restorative materials. Objective The aim of this study was to assess the performance of resin cements when different curing modes are used, by evaluating the degree of conversion and bond strength to a ceramic substrate. Material and Methods Three resin cements were evaluated, two dual-cured (Variolink II and RelyX ARC) and one light-cured (Variolink Veneer). The dual-cured resin cements were tested by using the dual activation mode (base and catalyst) and light-activation mode (base paste only). For degree of conversion (DC) (n=5), a 1.0 mm thick feldspathic ceramic disc was placed over the resin cement specimens and the set was light activated with a QTH unit. After 24 h storage, the DC was measured with Fourier transform infrared spectroscopy (FTIR). For microshear bond strength testing, five feldspathic ceramic discs were submitted to surface treatment, and three cylindrical resin cement specimens were bonded to each ceramic surface according to the experimental groups. After 24 h, microshear bond testing was performed at 0.5 mm/min crosshead speed until the failure. Data were submitted to one-way ANOVA followed by Tukey test (p<0.05). Scanning electron microscopy (SEM) was used for classifying the failure modes. Results Higher DC and bond strength values were shown by the resin cements cured by using the dual activation mode. The Variolink II group presented higher DC and bond strength values when using light-activation only when compared with the Variolink Veneer group. Conclusion The base paste of dual-cured resin cements in light-activation mode can be used for bonding translucent ceramic restorations of up to or less than 1.0 mm thick.